Studi Kerentanan Gerakan Massa Batuan dan Daerah Rawan Longsor Lahan di Kabupaten Purworejo - Sutarno Sutarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Title : Study of Mass Movement And Critical Landslide On Purworejo District. The objective of the research is to study of mass movement and critical landslide area and also agricultural area degradation in Purworejo. Research method use in the cheking the real condition and also deviation occuring in the field. The research result was the critical area of mass movement and landslide concentrated hilly and mountainous area spreading the nortern and eastern area at 9 Sub District Bruno, Kaligesing, Bagelen and some part of Bener, loano, Pituruh, kemiri and somepart of Purworejo City Sub District. The cause of the mass movement and critical landslide area is the very steep topography used for mixed agriculture area and high intensity rain. The protection conducted is by guidance for society to implement concervation and replanting and also to relocated the resettlement to a safety area.